Beyond art, beyond humanities, beyond technology: a new creativity - Brito, Claudio da Rocha (2012)
The history of humanity shows how important it is the communication made in many ways by means of art! Communication and arts aer part of human life in a daily basis such that it is necessary to attempt to the importance of communication of its many channels and now more than ever-in real time. Not to mention the art that expresses in many ways the beauty, the odd and the reflections of realities. The academic community dedicated to the search of science of communication and arts can count with an international forum for the discussions about communication and arts research. it is the WCCA´2012 - World Congress in Communication and Arts organized by COPEC - Science and Education Research the Thema of WCCA´2012: "Beyond Art, Beyond Humanities, Beyond Technology: A New Creativity" has brought researchers and professionals of theses areas to participate at the conference showing their interesting scientific works.